The AAST prospective Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery (AORTA) registry: Data on contemporary utilization and outcomes of aortic occlusion and resuscitative balloon occlusion of the aorta (REBOA). Issue 3 (September 2016) - DuBose, Joseph J.; Scalea, Thomas M.; Brenner, Megan; Skiada, Dimitra; Inaba, Kenji; Cannon, Jeremy; Moore, Laura; Holcomb, John; Turay, David; Arbabi, Cassra N.; Kirkpatrick, Andrew; Xiao, James; et al.
Abstract : INTRODUCTION: Aortic occlusion (AO) for resuscitation in traumatic shock remains controversial. Resuscitative endovascular balloon occlusion of the aorta (REBOA) offers an emerging alternative. METHODS: The American Association for the Surgery of Trauma Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery registry prospectively identified trauma patients requiring AO from eight ACS Level 1 centers. Presentation, intervention, and outcome variables were collected and analyzed to compare REBOA and open AO. RESULTS: From November 2013 to February 2015, 114 AO patients were captured (REBOA, 46; open AO, 68); 80.7% were male, and 62.3% were blunt injured. Aortic occlusion occurred in the emergency department (73.7%) or the operating room (26.3%). Hemodynamic improvement after AO was observed in 62.3% [REBOA, 67.4%; open OA, 61.8%); 36.0% achieving stability (systolic blood pressure consistently >90 mm Hg, >5 minutes); REBOA, 22 of 46 (47.8%); open OA, 19 of 68 (27.9%); p =0.014]. Resuscitative endovascular balloon occlusion of the aorta (REBOA) access was femoral cut-down (50%); US guided (10.9%) and percutaneous without imaging (28.3%). Deployment was achieved in Zones I (78.6%), II (2.4%), and III (19.0%). A second AO attempt was required in 9.6% [REBOA, 2 of 46 (4.3%); open OA, 9 of 68 (13.2%)]. Complications of REBOA were uncommon (pseudoaneurysm, 2.1%; embolism, 4.3%; limb ischemia, 0%). There was no difference in time to successful AO between REBOA and open procedures (REBOA, 6.6 ± 5.6 minutes; open OA, 7.2 ± 15.1; p = 0.842). Overall survival was 21.1% (24 of 114), with no significant difference between REBOA and open AO with regard to mortality [REBOA, 28.2% (13 of 46); open OA, 16.1% (11 of 68); p = 0.120]. CONCLUSION: Resuscitative endovascular balloon occlusion of the aorta has emerged as a viable alternative to open AO in centers that have developed this capability. Further maturation of the American Association for the Surgery of Trauma Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery database is required to better elucidate optimal indications and outcomes. LEVEL OF EVIDENCE: Therapeutic/care management study, level IV.